Developing E-module based on hypothetical inquiry learning to improve students' critical thinking skills - Sajidan, Sajidan; Jannah, Misbahul; Asnafiyah, Asnafiyah; Rizal, Setria Utama; Noris, M.; Suyitno, Margiyono (UIN Raden Mas Said Surakarta, 2025)
There is a scarcity of empirical studies that specifically examine the integration of Hypothetical Inquiry Learning (HIL) in e-modules to enhance students' critical thinking skills, particularly within the context of digital learning. This study aims to develop an e-module based on HIL to improve students' critical thinking abilities and the overall quality of learning in the digital era. The e-module is designed to facilitate students' understanding of complex concepts through an interactive Hypothetical Inquiry-based learning approach. The study employs a Research and Development (R&D) model based on Alessi and Trollip's framework, encompassing the Planning, Design, and Development stages. The study involved a population of 160 students, with a sample of 81 students from a senior high school in Sukoharjo regency, Central Java, Indonesia, and 5 validation experts, with validity assessed using the Aiken’s V index. The results of the practicality test demonstrated that the e-module based on HIL is highly practical for use as a digital learning tool, achieving a practicality score of approximately 98.32%. Furthermore, the effectiveness test revealed that the e-module significantly improves students' understanding of concepts and critical thinking skills, with an N-gain score of approximately 95.23%. Thus, the e-module based on Hypothetical Inquiry Learning represent an innovative and highly effective educational resource for enhancing student learning outcomes.